A Review on Azo Dyes Removal from Wastewater Using Biochar-Based Adsorbents: Materials, Mechanisms, and Perspectives - Navinda Ramadhan; Amanda Syafa Aliyah; Rabellia Juladika Sayeri; Neza Rahayu Palapa (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2025)
Azo dyes are synthetic organic pollutants widely used in the textile, food, leather, and cosmetic industries. Effluents containing these dyes are often discharged into the aquatic environment without adequate treatment, causing serious pollution that is toxic, carcinogenic, and resistant to biological degradation. Among various effluent treatment methods, adsorption stands out as an efficient, simple, and economical technique. Biochar a porous solid resulting from biomass pyrolysis has been of great interest as a potential adsorbent due to its superior physical-chemical properties and abundant raw material availability. This article reviews recent developments in the utilization of biochar, both natural and modified, for adsorption of azo dyes from wastewater. It discusses the mechanism of interaction between biochar and dye, operational factors that affect efficiency, and various biochar modification strategies such as chemical activation, metal addition, composite formation, and the use of nano-biochar. Data from various literatures show that the adsorption capacity of biochar towards Rhodamine B and Congo Red can reach more than 1000 mg/g, especially after advanced modifications. Nonetheless, technical and economic challenges in the widespread application of biochar still need to be overcome. This article provides an in-depth insight into the potential and future direction of biochar development as a sustainable solution in the treatment of wastewater polluted with azo dyes.